Effects of oral administration of the probiotic lactobacillus fermentum VRI-002 on the immune system of endurance athletes - Conway, P.; Pyne, D.; French, P.; Cox, A.; Saunders, P.; Fricker, P. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
A double-blind, placebo-controlled, cross-over trial was conducted to evaluate the capacity of the probiotic, Lactobacillus fermentum VRI-002, to enhance immune function. Twenty elite male distance runners were monitored over a four-month period of training and performance, mucosal and systemic immunity, and illness recorded. A highly significant reduction (p=0.0006) was observed in the number of days of respiratory symptoms reported during L. fermentum treatment compared with placebo. Similarly, illness severity scores tended to be lower for episodes occurring during the probiotic treatment (p=0.06) when compared with the placebo. There were no statically significant changes in training and performance measures over the study period, although athletes performed slight better on the treadmill when on L. fermentum compared to placebo. In seeking a mechanism at the clinical level to explain these results, some immune measures gave an indication of immune stimulus. An increase in IgA (p=0.73) amd IgA1 (p=0.14) during L fermentum administration was observed with a significant increase in interferon gamma after L fermentum treatment (p=0.00001). No significant changes in IL-12 and IL-4 concentrations in response to L. fermentum dosage were seen. It was conclude that prophylactic administration of L. fermentum was associated with a significant reduction in days of illness and severity of respiratory illness in a cohort of highly trained distance runners.